2021
DOI: 10.3390/ma14237468
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Current Limitations of Materials for Artificial Bile Duct Engineering

Abstract: Bile duct injury (BDI) and bile tract diseases are regarded as prominent challenges in hepatobiliary surgery due to the risk of severe complications. Hepatobiliary, pancreatic, and gastrointestinal surgery can inadvertently cause iatrogenic BDI. The commonly utilized clinical treatment of BDI is biliary-enteric anastomosis. However, removal of the Oddi sphincter, which serves as a valve control over the unidirectional flow of bile to the intestine, can result in complications such as reflux cholangitis, resten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Finally, inadequate vascularization is still the main obstacle to the long-term survival of bioengineered bile ducts. 152,153 If these limitations can be overcome, the clinical translation of bioengineered bile ducts will become feasible in the future.…”
Section: Adoptive Transfer Therapy For Biliary Regenerationmentioning
confidence: 99%
“…Finally, inadequate vascularization is still the main obstacle to the long-term survival of bioengineered bile ducts. 152,153 If these limitations can be overcome, the clinical translation of bioengineered bile ducts will become feasible in the future.…”
Section: Adoptive Transfer Therapy For Biliary Regenerationmentioning
confidence: 99%
“…The timing of stimulation of vascular growth is crucial for successful outcomes after graft implantation. Stimulation of angiogenesis has been shown to be especially important in the early period after scaffold implantation [ 13 , 14 , 15 , 16 ]. Previously, it was shown that the use of protein growth factors (fibroblast growth factors, epidermal growth factor, vascular endothelial growth factor (VEGF), platelet-derived growth factor, and other pro-angiogenic biomolecules) and gene therapy drugs, when applied locally, deposited on the surface of the material or embedded in the volume, promoted vascular growth in an implant [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of bile flow in the case of bile duct damage and biliodigestive anastomosis stricture still remains among the key challenges in modern medicine [ 1 , 2 , 3 ]. The use of balloon dilatation and plastic stent installation is not efficient enough because of their frequent migration from the bile duct lumen, the need for re-intervention every three months due to stent lumen obturation by the bile salts, and potential complications that may occur during their repeated placement [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the use of biocompatible and biodegradable materials for biliary stent construction is motivated by their degradability in natural conditions and incorporation into the lumen wall. Hence, biocompatible and biodegradable materials can be used for the formation of tissue-engineered grafts that may represent an alternative to stents and help to avoid the risk of stent migration [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%